A combined computational-fluid-dynamics model and control strategies for perfusion bioreactor systems in tissue engineering. Issue 3 (2021) - Nascu, Ioana; Sebastia-Saez, Daniel; Chen, Tao; Du, Wenli
Abstract: This work sets the foundations for the design of control algorithms to facilitate manufacturing of a cell growth process using a continuous perfusion bioreactor. The algorithms are designed to work with different types of cell cultures and deal with major disturbances that might appear in the process. Different types of control strategies are designed, implemented and tested. First, a comprehensive mathematical model of convection and diffusion in a perfusion bioreactor, combined with cell growth kinetics, is developed and implemented using Computational Fluid Dynamics. The model describes the spatio-temporal evolution of glucose concentration and cell density within a 3D polymeric scaffold. Since such a model is too complex to be used directly for control studies, a simplified version is used for the design of the controllers. Finally, the performances of the control strategies are validated against the original high-fidelity CFD model, thus closing the loop. The simulations show good performances and satisfactory behavior.